2019
DOI: 10.1097/hp.0000000000001131
|View full text |Cite
|
Sign up to set email alerts
|

Registry of Plutonium-induced Lung Fibrosis in a Russian Nuclear Worker Cohort

Abstract: A registry of plutonium-induced lung fibrosis diagnosed in members of a cohort of the first Russian nuclear industry facility Mayak Production Association was established. The registry includes 188 plutonium-induced lung fibrosis diagnoses: 117 (62.23%) in males and 71 (37.77%) in females. This paper describes the structure and detailed characteristics of the registry. Plutonium-induced lung fibrosis was shown to have no association with cumulative lung absorbed dose from external gamma rays as of the date of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Among those workers who could have been exposed to combined radiation (externally to gamma rays and internally to alpha particles) but had not been monitored, 66.3% (40.4%/77.2%) of the workers started employment at the Mayak PA between 1949 and 1959 and potentially could have received non-trivial (high) alpha doses from internal exposure. Here it should also be noted that some of these workers had died of plutonium-induced pulmonary fibrosis (Azizova et al 2019a) while some others had left the city before alpha exposure monitoring was implemented at the Mayak PA. Associated weaknesses of the study are uncertainties in alpha doses due to inaccuracies in bioassay alpha activity measurements and biases inherent to biokinetic and dosimetry models used to estimate alpha doses. These weaknesses limiting all studies of the Mayak PA worker cohort were pointed out in a number of previous papers.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Among those workers who could have been exposed to combined radiation (externally to gamma rays and internally to alpha particles) but had not been monitored, 66.3% (40.4%/77.2%) of the workers started employment at the Mayak PA between 1949 and 1959 and potentially could have received non-trivial (high) alpha doses from internal exposure. Here it should also be noted that some of these workers had died of plutonium-induced pulmonary fibrosis (Azizova et al 2019a) while some others had left the city before alpha exposure monitoring was implemented at the Mayak PA. Associated weaknesses of the study are uncertainties in alpha doses due to inaccuracies in bioassay alpha activity measurements and biases inherent to biokinetic and dosimetry models used to estimate alpha doses. These weaknesses limiting all studies of the Mayak PA worker cohort were pointed out in a number of previous papers.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…It appears that there is some dose threshold for pulmonary fibrosis, but estimates of this threshold vary by orders of magnitude, ranging from 0.5 Gy (10 Sv) (Newman et al 2005) to 6 Gy (Scott and Peterson 2003). The largest cohort of plutonium workers diagnosed with PuLF comes from the early days of the Mayak plutonium production facility, where 188 workers were diagnosed with PuLF (Azizova et al 2020). Of these, 54 cases were of combined etiology (plutonium exposure plus exposure to other toxins or risk factors), and for six workers, PuLF was a primary cause of death.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 54 cases were of combined etiology (plutonium exposure plus exposure to other toxins or risk factors), and for six workers, PuLF was a primary cause of death. The total radiation dose threshold for lung fibrosis is reported to be 4.0 Gy, although approximately 20% of workers with 1–3 Gy to the lungs from incorporated Pu were diagnosed with PuLF (Azizova et al 2020). In this cohort, it was found that the absorbed dose to the alveoloar-interstitial regions of the respiratory tract was a much better predictor of PuLF than the average absorbed dose to the whole lung.…”
Section: Discussionmentioning
confidence: 99%
“…In all 66 cases, the incorporated internal lung dose exceeded 4.0 Gy. Similarly, Azizova et al (2020) reported on a registry of 188 cases of plutonium-induced lung fibrosis among the Mayak worker cohort, and found that the incidence of lung fibrosis was associated with the cumulative lung absorbed dose from internally deposited alpha particles. A retrospective study of 326 plutonium-exposed and 194 unexposed Rocky Flats Plant nuclear workers (Newman et al 2005) The long-term retention of plutonium in the upper respiratory tract of USTUR Case 0269 can be explained by an assumption of a small bound fraction (Puncher et al 2017a, Birchall et al 2019.…”
Section: Literature Reviewmentioning
confidence: 93%
“…In addition to lung cancer, radiationinduced lung fibrosis-development of scar tissues in the connective tissue framework of the lungs-have been observed in experimental animals (Park et al 1964, Bair et al 1980, Sanders et al 1993, Wilson 2009, Nielsen et al 2012 and humans (Newman et al 2005, Azizova et al 2020Romanov et al 2020) in cases of large plutonium intakes. The deterministic effects such as lung fibrosis are expected to occur at doses beyond specific thresholds, and are more severe with larger absorbed doses (Scott and Peterson 2003, Newman et al 2005, Wilson 2009, Park et al 2012, Azizova et al 2020. The amounts and patterns of dose received by different lung tissues depend on retention time and location of plutonium in the lung, which in turn, are functions of several deposition, dissolution, and clearance parameters.…”
Section: Introductionmentioning
confidence: 99%